2017
DOI: 10.1007/s11332-017-0401-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of conventional and oval chainrings on patellofemoral loading during road cycling: an exploration using musculoskeletal simulation

Abstract: 16 PURPOSE:The aim of the current investigation was to utilize a musculoskeletal simulation 17 approach to resolve muscle forces during the pedal cycle, in order to specifically examine the 18 effects of chainring geometry on patellofemoral loading during cycling. RESULTS:No significant (P>0.05) differences in patellofemoral force or stress were found 26 throughout the pedal cycle between chainring conditions. It was also shown that no 27 significant (P>0.05) differences in patellofemoral force per 20 km joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The full text of 227 studies was retrieved and screened (figure 2). In total, 71 articles were included in the systematic review 25–95. There were 63 within-subject studies (56 healthy individuals, 7 patellofemoral pain), 1 randomised controlled trial in healthy individuals (online supplemental table 2) and…”
Section: Resultsmentioning
confidence: 99%
“…The full text of 227 studies was retrieved and screened (figure 2). In total, 71 articles were included in the systematic review 25–95. There were 63 within-subject studies (56 healthy individuals, 7 patellofemoral pain), 1 randomised controlled trial in healthy individuals (online supplemental table 2) and…”
Section: Resultsmentioning
confidence: 99%
“…The bicycle set-up was conducted in accordance with previous recommendations and maintained between each condition. The cycling shoes and cleats were also maintained across all trials (21).…”
Section: Methodsmentioning
confidence: 99%
“…The same biomechanical modelling approach as experiment 1 was utilized and five pedal cycles were examined in each condition during minutes 2-3. The pedal cycle was delineated using concurrent instances in which the right pedal was positioned at top dead centre, in accordance with Sinclair et al (21).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, they concluded that the oval chainring geometry might reduce the knee injuries. However, Sinclair et al [13] advise that the geometric chainring configurations do not appear to influence the patellofemoral force per 20 km joint during the pedal cycle. They found that the difference between the knee forces are not significant (around 8%) comparing the circular chainring with the oval one.…”
Section: Introductionmentioning
confidence: 99%